Metal-Free N-Formylation of Amines Using Carbohydrates as C1 Synthon via C–C Bond Cleavage - Atpadkar, Shital; Gill, Manjinder Singh (Synthesis, 2024)
Formamide group is an important part of many drug molecules, and herein a process for N-formylation of amines using carbohydrates as the C1 synthon under oxidative metal-free reaction conditions has been reported for the first time. Literature syntheses of formamides uses toxic, moisture sensitive and costly reagents under harsh reaction conditions. Our metal-free formylation is a facile, economical, and an efficient process of broad substrate scope that has led to the synthesis of thirty-three N-formylated compounds in excellent isolated yields.
Keywords: N-formylation; C1 synthon; metal-free; d-glucose